The stories of U.S.: nationalisms among college educated white women who voted in the 2016 U.S. presidential election - Strapko, Noel, author; Hempel, Lynn, advisor; Opsal, Tara, committee member; Lacy, Mike, committee member; McIvor, David, committee member (Colorado State University. Libraries, 2025)
Relatively recent sociological theories of nationalism understand the nation as variable processes whereby the nation is (re)constructed, albeit in different ways, via nationalism. Nationalism includes nation-oriented meanings and sentiments people embedded within socio-political contexts continually (re)formulate and imbue the nation with, which is how the nation is subjectively (re)created. Research on U.S. nationalism, however, primarily focuses on the subjective content of nationalism while the subjective contextualization of it remains understudied. In addition, although many aspects of nationalism are gendered, how women experience the nation and (re)create it is rarely examined. Addressing these gaps in the literature, this dissertation examines both the subjective content and the contextualization of U.S. nationalisms from the standpoint of college educated white women who voted in the 2016 presidential election. Utilizing in-depth, semi-structured qualitative interviews, I describe the various, yet patterned, ways America and Americans were constructed among interviewees and I examine the how they contextualized their expressions of nationalism. I argue "true" Americans' experiences with the American Dream were used to evaluate America's greatness, or lack thereof, which shaped the national sentiment the interviewees expressed. Findings provide key insight regarding: 1) the relevance of the American Dream for constructions of America, 2) how Americans and "true" Americans were constructed, 3) how gender relations, as well as those concerning other statuses, were used to contextualize nationalisms, 4) why expressions of nationalism can be ambivalent, and 5) how forms of nationalism are intertwined in constructions of American national membership.
Keywords: national membership; Nationalism; national sentiment; gendered nationalism